Altering the interfacial rheology of Pseudomonas aeruginosa and Staphylococcus aureus with N-acetyl cysteine and cysteamine - Balmuri, Sricharani Rao; Noaman, Sena; Usman, Huda; Niepa, Tagbo H. R. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Chronic lung infection due to bacterial biofilms is one of the leading causes of mortality in cystic fibrosis (CF) patients. Among many species colonizing the lung airways, Pseudomonas aeruginosa and Staphylococcus aureus are two virulent pathogens involved in mechanically robust biofilms that are difficult to eradicate using airway clearance techniques like lung lavage. To remove such biological materials, glycoside hydrolase-based compounds are commonly employed for targeting and breaking down the biofilm matrix, and subsequently increasing cell susceptibility to antibiotics. Materials and methods In this study, we evaluate the effects of N-acetyl cysteine (NAC) and Cysteamine (CYST) in disrupting interfacial bacterial films, targeting different components of the extracellular polymeric substances (EPS). We characterize the mechanics and structural integrity of the interfacial bacterial films using pendant drop elastometry and scanning electron microscopy. Results and discussion Our results show that the film architectures are compromised by treatment with disrupting agents for 6 h, which reduces film elasticity significantly. These effects are profound in the wild type and mucoid P. aeruginosa, compared to S. aureus. We further assess the effects of competition and cooperation between S. aureus and P. aeruginosa on the mechanics of composite interfacial films. Films of S. aureus and wild-type P. aeruginosa cocultures lose mechanical strength while those of S. aureus and mucoid P. aeruginosa exhibit improved storage modulus. Treatment with NAC and CYST reduces the elastic property of both composite films, owing to the drugs’ ability to disintegrate their EPS matrix. Overall, our results provide new insights into methods for assessing the efficacy of mucolytic agents against interfacial biofilms relevant to cystic fibrosis infection.